2021
DOI: 10.21037/qims-20-1356
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of conventional and deep learning methods for semi-automated segmentation of pulmonary nodules on CT

Abstract: Background: Accurate segmentation of pulmonary nodules on computed tomography (CT) scans plays a crucial role in the evaluation and management of patients with suspicion of lung cancer (LC). When performed manually, not only the process requires highly skilled operators, but is also tiresome and timeconsuming. To assist the physician in this task several automated and semi-automated methods have been proposed in the literature. In recent years, in particular, the appearance of deep learning has brought about m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 65 publications
0
19
0
Order By: Relevance
“…28 Bianconi et al discovered that deep learning is a viable approach for semi-automated segmentation of pulmonary nodules on CT scans. 26 However, these approaches presented some challenges. For semi-automated quantification methods, much larger datasets were needed to complete the calculation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 Bianconi et al discovered that deep learning is a viable approach for semi-automated segmentation of pulmonary nodules on CT scans. 26 However, these approaches presented some challenges. For semi-automated quantification methods, much larger datasets were needed to complete the calculation.…”
Section: Discussionmentioning
confidence: 99%
“…24 Semi-automated quantification methods with radiomics could reduce the false positive results significantly. [25][26][27] Spanu et al found that TF SPECT was a highly accurate diagnostic method in the detection of intrathoracic malignant lesions. 28 Bianconi et al discovered that deep learning is a viable approach for semi-automated segmentation of pulmonary nodules on CT scans.…”
Section: Discussionmentioning
confidence: 99%
“…However, for some features simple mathematical transformations could be applied to make the features independent of the number of quantisation levels (see for instance Appendix A ). In order to avoid or reduce the inter-observer bias related to manual lesion delineation, automated and semi-automated methods offer great promises in terms of speed, accuracy and repeatability [ 65 ]. Previous studies have shown that semi-automated segmenters can improve on manual delineation and generate more reproducible radiomics features [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Accurate nodule volumetry requires good nodule segmentation. Manual segmentation of lung nodules is time consuming and is far less accurate in comparison to deep learning semiautomated methods [ 120 ]. Most of the available algorithms concerned with pulmonary nodule detection rely on growing edge method where a predefined threshold acts as a seed that connects all nearby voxels of higher density [ 121 ].…”
Section: Pulmonary Nodule Detection and Segmentationmentioning
confidence: 99%